Time and chance - Penman, Sharon Kay (Ballantine Books, 2003)
In When Christ and His Saints Slept, acclaimed historical novelist Sharon Kay Penman portrayed all the deceit, danger, and drama of Henry II's ascension to the throne. Now, in Time and Chance, she continues the ever-more-captivating tale. It was medieval England's immortal marriage-Eleanor of Aquitaine and Henry II, bound by passion and ambition, certain to leave a legacy of greatness. But while lust would divide them, it was friendship-and ultimately faith-that brought bloodshed into their midst. It began with Thomas Becket, Henry's closest confidant, and his elevation to be Archbishop of Canterbury. It ended with a perceived betrayal that made a royal murder seem inevitable. Along the way were enough scheming, seductions, and scandals to topple any kingdom but their own. Only Sharon Kay Penman can re-create this truly tumultuous time-and capture the couple who loved power as much as each other, and a man who loved God most of all.